Enterococcus species: insights into antimicrobial resistance and whole-genome features of isolates recovered from livestock and raw meat in Ghana - Amuasi, Grebstad Rabbi; Dsani, Esther; Owusu-Nyantakyi, Christian; Owusu, Felicia A.; Mohktar, Quaneeta; Nilsson, Pernille; Adu, Bright; Hendriksen, Rene S.; Egyir, Beverly (Frontiers in Microbiology, 2023)
Introduction: Enterococcus spp. have gradually evolved from commensals to causing life-threatening hospital-acquired infections globally due to their inherent antimicrobial resistance ability and virulence potential. Enterococcus spp. recovered from livestock and raw meat samples were characterized using antimicrobial susceptibility testing and whole-genome sequencing.Isolates were confirmed using the MALDI-ToF mass spectrometer, and antimicrobial susceptibility was determined using the Kirby-Bauer disk diffusion method. Whole genome sequencing was performed on isolates resistant to two or more antibiotics. Bioinformatics 2 analysis was performed to determine sequence types, resistance and virulence gene content and evolutionary relationships between isolates from meat and livestock samples, and other enterococci genomes curated by PATRIC. eBURST analysis was used to assign genomes to clonal complexes.: Enterococcus spp. were predominantly E. faecalis (96/236; 41%) and E. faecium (89/236; 38%). Overall, isolates showed resistance to erythromycin (78/236; 33%), tetracycline (71/236; 30%), ciprofloxacin (20/236; 8%), chloramphenicol (12/236; 5%), linezolid (7/236; 3%), ampicillin (4/236; 2%) and vancomycin (1/236; 0.4%). Resistance to two or more antimicrobial agents was detected among 17% (n=40) Enterococcus spp. Resistance genes for streptogramins [lsa(A), lsa(E), msr(C)], aminoglycosides [aac(6')-Ii, aph(3')-III, ant(6)-Ia, aac(6')-aph(2''), str], amphenicol [cat], macrolideswere detected among the isolates. Genes for biofilm formation, adhesins, sex pheromones, cytolysins, hyaluronidase, oxidative stress resistance, quorum-sensing and anti-phagocytic activity were also identified. Potential plasmids with replicon sequences (rep1, rep2, repUS43, repUS47, rep9a, rep9b) and other mobile genetic elements (Tn917, cn_5536_ISEnfa1, Tn6009, ISEnfa1, ISEfa10) were detected. Clinically relevant E. faecium ST32 and ST416 clones were identified in meat samples.The occurrence of antimicrobial-resistant Enterococcus spp. in livestock and raw meat samples, carrying multiple resistance and virulence genes, including known clones associated with hospital-acquired infections, underscores the critical need for employing robust tools like whole genome sequencing. Such tools provide detailed data essential for ongoing surveillance efforts aimed at addressing the challenge of antimicrobial resistance with a focus on one health.